Behavioral changes to detect estrus using ear-sensor accelerometer compared to in-line milk progesterone in a commercial dairy herd - Perez Marquez, Hector J.; Ambrose, Divakar J.; Bench, Clover J. (Frontiers in Animal Science, 2023)
The first objective of this study was to compare behavioral and ear temperature changes using accelerometer ear tags (CowManager system; Sensor) during the declining progesterone (P4) phase (expected estrus) and the luteal phase determined using in-line milk P4 analysis (Herd Navigator system; HNS). The second objective was to evaluate the accuracy of each Sensor metric to detect estrus compared to HNS in a commercial dairy herd. Forty-six cows (23 young [1 to 2 lactations] and 23 mature [3 to 6 lactations]) at 20 days in milk (DIM) were fitted with Sensor tags, and P4 profiles measured via HNS until 90 DIM. Sensor metrics analyzed were Resting, Ruminating, Eating, Active, High-Active, and ear temperature (Etemp). The day of milk P4 decline below the 5 ng/mL threshold in the HNS was designated as d -1 (LSM ± SEM; 3.42 ± 0.08 ng/mL) and the day of expected estrus as d 0. Significant increases (LSM ± SEM) were observed at d 0 in Active (5.01 ± 0.14 min/h) and High-Active (8.70 ± 0.25 min/h) behavior responses as well as in Etemp (29.45 ± 0.08 °C) compared with the luteal phase (Active: 4.46 ± 0.13 min/h; High-Active: 6.40 ± 0.22 min/h and Etemp: 28.69 ± 0.08 °C). The greatest estrus detection accuracy (Youden Index [J: performance]) single metric was achieved using Etemp (0.24 J) followed by Resting (0.20 J) and High-Active (0.17 J) in all cows. Greater accuracy was observed in young cows (Etemp: 0.44 J; Resting: 0.33 J; and High-Active: 0.25 J) than in mature cows (Etemp: 0.09 J; Resting: 0.12 J; and High-Active: 0.13 J). Similarly, accuracy was greater when only healthy cows (cows with no postpartum health events) were compared (Etemp: 0.33 J; Resting: 0.31 J; High-Active: 0.20 J) to unhealthy cows (Etemp: 0.11 J; Resting: 0.02 J; High-Active: 0.02 J). The combination of behavior and Etemp metrics optimized the estrus detection accuracy in all the cows (0.30 J), Young (0.46 J), Mature (0.26 J), Healthy (0.45 J), and Unhealthy (0.11 J) cows compared to a single metric approach. Age and postpartum health affected the estrus detection accuracy using Sensor tags.